Online Multicultural Guidance and Counseling Based On Islamic Boarding Schools with the Utilization of Hand Sanitizer - Najlatun Naqiyah; Budi Purwoko; Bambang Dibyo Wiyono (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
In the new normal era, students lived in Islamic boarding schools. In the COVID-19 with a high number of corona positives, it was necessary to be prepared with the health protocol. Students take classical guidance exercises on the topic of living assignments to make peace with COVID-19. The material will be developed online which is easily accessed by students. The multicultural guidance method is carried out using a classical model with the topic of assignments. Data collection was carried out on 17 children who live in Islamic boarding schools. Ages 13-20 years are junior high school and senior secondary level. Data collection using observation and assessment. The counselor is a direct participant who is involved with the students in their daily lives at the Islamic boarding school who makes direct observations. Data collection was also carried out using observation sheets when assignments were made presentations every week for 8 meetings. Multicultural guidance can improve students' skills to accept reality with a sincere, attitude and help others to adhere to each other's health protocols, use masks, wash hands frequently, hand sanitizers, keep a distance by maintaining immunity.